School Culture and Teacher Performance: A Comprehensive Review Through a Modeling Approach (Systematic Literature Review) - Rosida Rosida; Bambang Budi Wiyono; Aan Fardani Ubaidillah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to analyze the role of school culture in improving teacher performance through a Systematic Literature Review (SLR) approach to twenty relevant scientific articles from the past ten years. The results of the analysis indicate that a positive school culture, characterized by the values of religiosity, integrity, mutual cooperation, and strong transformational leadership, can create a conducive work environment and increase teacher motivation, commitment, and professionalism. Other factors such as effective communication and professional development through regular training have also been shown to contribute to improved teacher performance. However, the results also reveal a significant gap, namely the lack of comprehensive integration between school culture and institutional policies systematically to support sustainable teacher performance improvement. Furthermore, there is little research exploring the challenges of implementing school culture in the context of inclusive schools or areas with limited resources. Therefore, further empirical and contextual studies are needed to formulate operational strategies to strengthen school culture oriented towards improving teacher performance and the overall quality of education.